2015
DOI: 10.2105/ajph.2014.302391
|View full text |Cite
|
Sign up to set email alerts
|

Suicide Ideation and Bullying Among US Adolescents: Examining the Intersections of Sexual Orientation, Gender, and Race/Ethnicity

Abstract: Future research should examine how adolescents' intersecting identities shape their experience of victimization and suicidality. School personnel should develop antibullying and antihomophobia policies in response to the disproportionate risk of being bullied and reporting suicidality among sexual minority youths.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

10
108
1
2

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 160 publications
(121 citation statements)
references
References 34 publications
10
108
1
2
Order By: Relevance
“…More than half of youth who qualified as traditional bullies and cyberbullies had clinically significant anxiety scores and clinically significant depression (Price et al, 2013). Youths who are bullied are more likely to report depression, low self-esteem, poor school performance, and suicide attempts; being bullied is also associated with higher odds of suicidal ideation, regardless of an adolescent's gender, race/ethnicity, or sexual orientation (Bhatta, Shakya, & Jefferis, 2014;Mueller, James, Abrutyn, & Levin, 2015;Sampasa-Kayinga et al, 2014).…”
Section: Mental Health Effectsmentioning
confidence: 99%
“…More than half of youth who qualified as traditional bullies and cyberbullies had clinically significant anxiety scores and clinically significant depression (Price et al, 2013). Youths who are bullied are more likely to report depression, low self-esteem, poor school performance, and suicide attempts; being bullied is also associated with higher odds of suicidal ideation, regardless of an adolescent's gender, race/ethnicity, or sexual orientation (Bhatta, Shakya, & Jefferis, 2014;Mueller, James, Abrutyn, & Levin, 2015;Sampasa-Kayinga et al, 2014).…”
Section: Mental Health Effectsmentioning
confidence: 99%
“…Furthermore, they found that sexual minority, gender, and ethnic identities interacted with bullying to predict participants who reported a suicide attempt. In a similar study, Mueller et al (2015) examined the intersection of race, gender, sexual orientation and suicidality. They found that White and Hispanic gay and bisexual males, White lesbian and bisexual females, and Hispanic bisexual females were more likely to report being bullied than were White heterosexual adolescents.…”
Section: Sexual Orientation Victimization and Suicidalitymentioning
confidence: 99%
“…Bullying victimization is a common social determinant of health among adolescents, with 8% of 15 year olds surveyed in 37 countries reporting at least two episodes of bullying victimization in the previous “few” months (WHO, ). Research has shown that bullying victims have a significantly greater risk of depression (Bowes, Joinson, Wolke, & Lewis, ), suicide (Bauman et al, ; Messias et al, ; Mueller et al, ; Sibold et al, ; Van Geel et al, ), substance use (Valdebenito, Ttofi, & Eisner, ), sexual risk‐taking (Hertz, Everett, Barrios, David‐Ferdon, & Holt, ), school avoidance (Hutzell & Payne, ) and other psychological and behavioral problems (Litwiller & Brausch, ; Olweus, ). Because of the numerous associated negative health outcomes, including suicidality (Bauman et al, ; Messias et al, ; Mueller et al, ; Sibold et al, ; Van Geel et al, ), greater attention has been given to address this form of victimization, especially now that new forms of bullying victimization are possible through social media.…”
Section: Introductionmentioning
confidence: 99%